Numerical Study of Orifice Plate in Entrance and Fully-Developed Flow Region for Fluid Flow Measurement - Irdam, Fortinov Akbar; Tanjung, Munir; Akhyan, Amnur (DINAMIS, 2025)
Having reliable data is important for analyzing the fluid behaviour inside the pipe. Hence, the selection of the fluid flow measurement instrument becomes critical to fulfill its objectives. Orifice plate, one of the pressure-based device is commonly used for its simplicity and ease of use. One of the phenomena that occurs during the flow measurement process using an orifice plate is the pressure drop between its upstream and downstream regions. Many researchers have brought this topic to find the best solution to reduce the pressure drop impacts to fluid flow for both experimental and numerical analysis. Understanding the pressure drop situation of the orifice plate in the entrance region and fully-developed flow region remains a relatively unanimous topic. A numerical study is conducted on this research to find the influence of the orifice plate’s thickness and the location of the installation of the orifice plate on the fluid flow to the pressure difference in the upstream and downstream sides of the orifice plate. The results show that the pressure drop at its highest will happen when a thicker orifice plate is chosen and it is located in the entrance region. This result will hopefully give better insight for orifice plate research in order to reduce pressure drop in fluid flow, which could ultimately increase the efficiency of the process of fluid flow inside the pipe. Future work can be expanded to study the orifice plate’s mechanical behaviour due to pressure from fluid flow.